Immune Response 5-7 Months after Vaccination against SARS-CoV-2 in Elderly Nursing Home Residents in the Czech Republic: Comparison of Three Vaccines - Martínek, Jan; Tomášková, Hana; Janošek, Jaroslav; Zelená, Hana; Kloudová, Alena; Mrázek, Jakub; Ježo, Eduard; Král, Vlastimil; Pohořská, Jitka; Šturcová, Hana; Maďar, Rastislav (Viruses, 2022)
BACKGROUND AND AIMS: Elderly nursing home residents are especially prone to a severe course of SARS-CoV-2 infection. In this study, we aimed to investigate the complex immune response after vaccination depending on the convalescence status and vaccine. METHODS: Sampling took place in September-October 2021. IgG antibodies against spike protein and nucleocapsid protein, the titer of virus neutralization antibodies against delta and (on a subset of patients) omicron, and cellular immunity (interferon-gamma release assay) were tested in nursing home residents vaccinated with Pfizer, Moderna (both 30-31 weeks after the completion of vaccination), or AstraZeneca (23 weeks) vaccines. The prevalence with 95% confidence intervals (CI) was evaluated in Stata version 17. RESULTS: 95.2% (95% CI: 92.5-97.1%) of the 375 participants had positive results of anti-S IgG, 92.8% (95% CI: 89.7-95.2%) were positive in virus neutralization assay against delta, and 89.0% (95% CI: 84.5-92.5%) in the interferon-gamma-releasing assay detecting cellular immunity. Results of the virus neutralization assay against omicron correlated with those against delta but the neutralization capacity was reduced by about half. As expected, the worst results were found for the AstraZeneca vaccine, although the vaccination-to-test period was the shortest for this vaccine. All immune parameters were significantly higher in convalescent residents than in naive residents after vaccination. No case of COVID-19 occurred during the vaccination-to-test period. CONCLUSIONS: A high immune response, especially among vaccinated convalescents (i.e., residents with hybrid immunity), was found in elderly nursing home residents 5-7 months after vaccination against SARS-CoV-2. In view of this, it appears that such residents are much better protected from COVID-19 than those who are only vaccinated and the matter of individual approach to the booster dose in such individuals should be further discussed.
Keywords: vakcíny; imunita; Immunity; Aged; COVID-19; vakcinace; Nursing Homes; Humans; Česká republika; SARS-CoV-2; senioři; lidé; Immunoglobulin G; pečovatelské domovy; imunoglobulin G; Vaccines; Czech Republic; Vaccination